Optimization Objective Function Corona Discharge Acoustic Using Fuzzy c-Means (FcM ) - Fikri, Miftahul; Christiono, Christiono; Mulyana K, Iwa Garniwa; Ratnasari, Titi; Atmadja, Kurniawan; Thahara, Andi Amar; Romadhoni, Muhammad Luthfiansyah (ELKHA : Jurnal Teknik Elektro, 2023)
In many electrical networks in Indonesia, insulation failure due to high voltage phenomena like Corona Discharge (CD) still happens. This is a result of our inability to perform early Corona Discharge (CD) identification. This study"™s objective is to optimalize the sound properties of Corona Discharge (CD) as a first step throught the early identification of insulation failure in the form of clustering 20 kV cubicle. Based on observations on the needle-rod electrode 3 cm apart, the smallest breakdown was obtained at 34.3 kV. So that the classification of CD sound by 3 clusters starting 20 kV cubicle voltage until before the failure occurs on 33 kV. The temperature in the cubical is between 27.5â„ƒ - 35.3â„ƒ and humidity ranges from 70% - 95%. It was stated in the study that the FcM method was the most widely used and successful method. In this case, FcM can obtain more flexible results that classify data into clusters easily. This research will be carried out using the Fuzzy c-Means (FcM) method. Feature extraction with linear predictive coding (LPC) method, then optimization by using the Fuzzy c-Means (FcM) method which is expected to be used as an initial step for early detection of insulation failure.